EARLY IDENTIFICATION OF SPECIFIC LEARNING DISABILITY: CASE STUDY ON SECOND GRADE ELEMENTARY SCHOOL STUDENTS WITH UNDERACHIEVEMENT - Shinta Malida Balqis; Endang Rochyadi; Tjutju Soendari (JPSD (Jurnal Pendidikan Sekolah Dasar), 2021)
Abstract Introduction, The purpose of this study is description an objective result of Assessment for Learning and Modality Profiling who early identified student with Specific Learning Disability (SpLD/LD). Objectives, Participants in this study were 25 students (13 boys and 12 girls) in second grade elementary school (Ages 8-9 years old) with 24 non-disability students and one student with motoric disability, class room teacher, parents, and headmaster. Method, Using case study this research describes five of the eight steps of the Special Education Approach: (1) Screening, (2) Evaluation, (3) Eligibility Determination, (4) Individualized Educational Program (IEP) Meeting, and (5) Write IEP. Findings, Students who showed frustration level in the result of the Academic Assessment (Reading, Writing, and Math) were 38% (62,5% for one skill and 37,5% for all the skills). With the result of the developmental Assessment of DVA (L) and JML (L) there were no obstacles, while RST (L) was identified as having obstacles in skills of social, cognitive (correspondence and conservation), perception, and Language (pronunciation). Conclusions, To identified as SpLD the students need multidisciplinary approach. Modality Profiling for underachiever to provide the earliest intervention, so there is an increase in learning outcomes.Keywords: Learning Disability; Assessment; Modality Profiling.